Analisis Akad Jual Beli Properti dengan Sistem Pembayaran Cash Bertahap - Yayat Rahmat Hidayat; Selva Nur Fadhilah; Shakila Charisya Tsania (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Islamic property developers are currently starting to offer housing with the sharia financing model. One of them is Nuansa Alam Setiabudi Clove who sells his house using an istishna contract, does not use bank financing, without confiscation, and fines. The payment methods used are cash and cash in stages. In its implementation, there are cases where the buyer does not make payments in succession within the agreed time frame at the time of the contract, which results in losses to the developer. The purpose of this study is to analyze the implementation and solution to the problem of buying and selling Islamic properties with the cash payment method in stages. This research is a qualitative study using a case study approach. The data analysis technique used descriptive analysis method. The results of the study found that the contract construction made by the developer needs to be improved and added, namely in Article 5 concerning Late Payment, Article 7 concerning Contract Cancellation and Compensation, and Article 8 concerning Dispute Resolution, to avoid losses caused by a bankless sales system, without confiscation, and without penalty.